Capacity development in pursuit of social change: an examination of processes and outcomes. Issue 4 (19th May 2022) - Aantjes, Carolien Jeanette; Burrows, Dave; Armstrong, Russell
ABSTRACT: Understanding "what works" for capacity development support in an international development setting remains an important area for operational research. This mixed-methods study explored this topic within a global programme that supports civil society organisations in fifteen countries to secure the health and human rights of marginalised and underserved populations. Taking a complex adaptive systems approach, and seeking to understand the phenomena from the "receiver" perspective, the study found that the programme fostered the development of four interconnected domains of capacity through a reflexive, user-led approach. These capacity gains could be linked, although not causally, to important programmatic achievements for the programme's focus populations.